SIRT1 regulates oxidant- and cigarette smoke-induced eNOS acetylation in endothelial cells: Role of resveratrol - Arunachalam, Gnanapragasam (2010)
Endothelial nitric oxide synthase (eNOS) plays a crucial role in endothelial cell functions. SIRT1, a NAD(+)-dependent deacetylase, is shown to regulate endothelial function and hence any alteration in endothelial SIRT1 will affect normal vascular physiology. Cigarette smoke (CS)-mediated oxidative stress is implicated in endothelial dysfunction. However, the role of SIRT1 in regulation of eNOS by CS and oxidants are not known. We hypothesized that CS-mediated oxidative stress downregulates SIRT1 leading to acetylation of eNOS which results in reduced nitric oxide (NO)-mediated signaling and endothelial dysfunction. Human umbilical vascular endothelial cells (HUVECs) exposed to cigarette smoke extract (CSE) and H(2)O(2) showed decreased SIRT1 levels, activity, but increased phosphorylation concomitant with increased eNOS acetylation. Pre-treatment of endothelial cells with resveratrol significantly attenuated the CSE- and oxidant-mediated SIRT1 levels and eNOS acetylation. These findings suggest that oxidant-mediated reduction of SIRT1 is associated with acetylation of eNOS which have implications in endothelial dysfunction.